Creolization and cultural globalization: the soft sounds of fugitive power - Cohen, R (Routledge, 2007)
In this article, I provide a comparative discussion of Creoles and creolization. The core concept centres on the cross-fertilization between different cultures as they interact. When creolization occurs, participants select particular elements from the incoming or inherited cultures, endow these with meanings different from those they possessed in the original cultures, and then creatively merge these to create new varieties that supersede the prior forms. While discussions of creolization are common in linguistics, studies of popular culture, and historical studies of certain plantation societies, I use the notion here as a contemporary and general sociological term. I argue that creolization is a key aspect of cultural globalization and provide more detailed discussion of new understandings of creolization in Brazil, Sout Africa, and the US. I contrast manifest and strident forms of 'monocultural' power in the reassertion of nationalism, narrow ethnicities, and religious affinities with the more subtle but pervasive forms of 'fugitive power' found in the construction and affirmation of creolized identities. Creolization is only one aspect of fugitive power, but it is one with an intriguing past, an increasingly visible present and, I will suggest, a promising future. En este artículo, planteo un tema comparativo sobre los criollos y la criollización. El concepto primordial se centra en el intercambio de differentes culturas cuando interactúan. Cuando ocurre la criollizaci ón, los participantes seleccionan elementos particulares de culturas inherentes o de afuera, los dotan con significados differentes de aquellos que poseían en las culturas originales y luengo los incorporan creativamente para crear nuevas variedades que reemplazan a las formas anteriores. Mientras que los debates sobre la criollización son communes en lingüstíca, los estudios sobre la cultura popular y los estudios históricos de ciertas sociedades de las plantaciones, yo uso aquí la noción como un término contemporáneo y sociológico general. Sostengo que la criollización es un aspecto clave de la globalización cultural y que provee más argumentos detallados de los nuevos entendimientos de la criollización en el Brasil, Sud áfrica y los EE. UU. Yo establezco un contraste entre las formas manifiestas y estridentes del poder 'monocultural' en la reiteración del nacionalismo, etnicidades estrechas y las afinidades religiosas, con las formas más sutiles pero persuasivas del 'poder fugitivo' halledo en la creación y affirmación de identidades criollizadas. La criollización es solamente un aspecto del poder fugitivo, pero con un pasado intrigante, un presente cada vez más visible y yo sugeriría, un futuro prometedor.